2000
DOI: 10.1007/s002090050489
|View full text |Cite
|
Sign up to set email alerts
|

The number of simple modules of the Hecke algebras of type G ( r ,1, n )

Abstract: This paper classifies the simple modules of the cyclotomic Hecke algebras of type G(r, 1, n) and the affine Hecke algebras of type A in arbitrary characteristic. We do this by first showing that the simple modules of the cyclotomic Hecke algebras are indexed by the set of "Kleshchev multipartitions".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
186
0
7

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(198 citation statements)
references
References 22 publications
5
186
0
7
Order By: Relevance
“…We remark that the irreducible representations of the Ariki-Koike algebras are indexed by the u-Kleshchev multipartitions; see [Ari01,AM00]. In the special case when u i = d i · 1 R , for 1 ≤ i ≤ r and where 0 ≤ d i < char R, Kleshchev [Kle05] has shown that the simple H r,n (u)-modules are labelled by a set of multipartitions which gives the same Kashiwara crystal as the set of u-Kleshchev multipartitions of n. Hence, in this case, the simple W r,n (u)-modules are labelled by the set {(f, λ)}, where 0 ≤ f ≤ ⌊ We close by classifying the quasi-hereditary cyclotomic Nazarov-Wenzl algebras with ω 0 = 0.…”
Section: Classification Of the Irreducible W Rn -Modulesmentioning
confidence: 99%
“…We remark that the irreducible representations of the Ariki-Koike algebras are indexed by the u-Kleshchev multipartitions; see [Ari01,AM00]. In the special case when u i = d i · 1 R , for 1 ≤ i ≤ r and where 0 ≤ d i < char R, Kleshchev [Kle05] has shown that the simple H r,n (u)-modules are labelled by a set of multipartitions which gives the same Kashiwara crystal as the set of u-Kleshchev multipartitions of n. Hence, in this case, the simple W r,n (u)-modules are labelled by the set {(f, λ)}, where 0 ≤ f ≤ ⌊ We close by classifying the quasi-hereditary cyclotomic Nazarov-Wenzl algebras with ω 0 = 0.…”
Section: Classification Of the Irreducible W Rn -Modulesmentioning
confidence: 99%
“…The definition of regular bipartitions is quite complicated in general, and depends on q and Q; the original recursive definition [AM1] is derived from the theory of crystals. In the case e = ∞, it is easy to derive a non-recursive definition.…”
Section: Beta-setsmentioning
confidence: 99%
“…In particular, in our H q (p, n) case, q must be a root of unity. To state the result of Ariki, we have to recall the definition of the Kleshchev multipartition (see [7]). For any p-multipartition λ, the Young diagram of λ is the set It has five removable nodes.…”
Section: Theorem 23 ([15 Theorem 11]) With the Above Notations Tmentioning
confidence: 99%
“…They give a characterization of τ in terms of ω and a bijection κ between the set of Kleshchev multipartitions and the set of FLOTW partitions (see [20,Proposition 2.9, lines 3-4 on page 14]). Note that our description of h in (3.11) is actually a statement about the crystal graph, and although [20] uses JMMO's Fock space ( [30], [16]) and we use Hayashi's Fock space ( [22], [7]), the two crystals provided by the lattice of Kleshchev multipartitions and by the lattice of FLOTW partitions respectively are isomorphic to each other. It follows that the description of h in (3.11) in the context of Kleshchev's good lattices should also be valid in the context of FLOTW's good lattices.…”
Section: Defines a Path In Kleshchev's Good Lattice With Respect Tomentioning
confidence: 99%
See 1 more Smart Citation